1982
DOI: 10.1021/ar00082a004
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the imidazolate-bridged bimetallic center in the copper-zinc superoxide dismutase and its model compounds

Abstract: Ligand-bridged polymetallic centers occur in numerous metalloproteins where they perform electron transfer, oxygen transport, and catalytic redox functions.1 The properties of a variety of proteins containing such centers are given in Table I.2-10 One of the most extensively studied members of this group, and probably the best understood, is the Cu-Zn superoxide dismutase (SOD+).Superoxide dismutases are a ubiquitous group of enzymes. Procaryotes and mitochondria of eucaryotic cells have ironor manganese-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 52 publications
2
79
0
Order By: Relevance
“…Strothkamp and Lippard, 1982). It was suggested that reduction of the copper is accompanied by displacement and protonation of the bridging imidazolate side chain.…”
Section: Superoxide Dismutasementioning
confidence: 99%
“…Strothkamp and Lippard, 1982). It was suggested that reduction of the copper is accompanied by displacement and protonation of the bridging imidazolate side chain.…”
Section: Superoxide Dismutasementioning
confidence: 99%
“…Particularly, interest in imidazole-containing complexes is credited to the large number of active sites in copper proteins where this group is observed [5]. Except for the copper(I)-thioneins, all the copper proteins studied so far exhibited imidazole residues of histidine bounded to the metal center, especially those related to molecular oxygen transport, or activation [6].…”
Section: Imine Copper(ii) Complexes Have Been Extensivelymentioning
confidence: 99%
“…In many copper proteins and enzymes, the imidazole ring is an essential metal binding site, and thus a wide variety of imidazole containing ligands have been investigated to mimic structural features of these biomolecules (Strothkamp & Lippard 1982). In our case, some dinuclear copper complexes with a tridentate diimine ligand, in addition to an imidazole as the bridging ligand, were prepared, characterized, and had their catalytic properties investigated.…”
Section: Mimics Of Proteins With Dicopper Sitesmentioning
confidence: 99%